Analisis Terjemahan Tarkīb Iḍāfī Surah Al-Qiyamah - Rahmatullah, Afdhal; Faizi, Muhamad Raihan (Study Program of Arabic Language Teaching, 2023)
Tarkīb iḍāfah is the merging of two nouns into one sentence that causes one of the nouns to be read separately. In tarkīb iḍāfah, there are three types of meaning, namely possession (lām), origin/ source (min/ bayāniyyah), and time/place (fī/ ẓarfiyah). The requirement for muḍāf nouns is that they must be free from al ta'rif and tanwin, while muḍāf ilaih nouns are allowed to use al ta'rif or tanwin. The purpose of this study is to describe (1) the types of tarkīb iḍāfah contained in Surat Al-Qiyamah, (2) the function of tarkīb iḍāfah in Surat Al-Qiyamah, and (3) the meaning contained in tarkīb iḍāfah in Surat Al-Qiyamah. This study used the qualitative descriptive method. The research data used is tarkib idhafah contained in Surah Al-Qiyamah. The results showed that there are 16 tarkīb iḍāfah in Surat Al-Qiyamah. Of the 16 tarkīb iḍāfah, 14 of them have muḍāf ilaih in the form of a noun that contains the meaning of tarkīb lām, which is possession. Meanwhile, the other two tarkīb iḍāfah have muḍāf ilaih in the form of a noun that has the meaning tarkīb fī, which indicates time/era.